Analisis Kebutuhan Tenaga Rekam Medis dengan Metode Workload Indicator Staffing Need (WISN) - Ria Chandra Kartika; Effa Tuzzakiyah; Dessya Putri Ayu; Dina Fitriyah; Surya Dewi Puspita (Jurnal Rekam Medik & Manajemen Informasi Kesehatan, 2022)
As the enacment of National Healt Coverage (JKN), certaintly the number of patients who seek treatment in hospitals has increase due to the patient no longer think about the cost of an expensive problem. The occurrence of the coopertion between the BPJS Paru Hospital Surabaya, certainly made a number of cisits increases it can be seen in the increase in the number of cisits the patient in Paru Hospitals Surabaya years 2014 to 2016. Calculatio of the new workforce needs in the unit procedures is indispensable in order to improve the quality of service. If the increasing number of visits certainly have an effect on basic tasks performed by officers of the procedures. Therefore required the calculation of labbor needs on the Unit Procedures Paru Hospital Surabaya. Type of this research is descriptive, by describing the calculation of labor needs medical record on the Unit Procedures tah the Paru Hospital Surabaya. Data collection methods used in this study. Interview Procedures and observations officer to find out the acerage time taken at each activity. From the results of research on workforce needs calculation Unit Procedures Paru Hospital Surabaya found to shift the morning amoun ted to 3 officers. Ther result is greater compared to the number of staff available at this time. If the number of officers alreay according to needs will facilitate the pro cess of service to patients and improven the quality of work.